Making the grass greener The role of firm's financial and managerial capacity in paving the way for the green transition - Costa, Hélia (OECD Economics Department Working Papers, 2024)
Despite the ambitious carbon reduction targets set by policy makers worldwide, current investments fall well short of the net-zero emissions scenario. This paper analyses the factors holding back corporate green investment, with a particular focus on the role of firm capacity - specifically financing constraints and weak green management practices - and its interaction with environmental policy. Combining a variety of econometric techniques, including panel data models, difference-in-differences settings and instrumental variable approaches, our cross-country analysis on large listed companies shows that: i) both financing constraints and a lack of green managerial capacity reduce firms' probability of investing in green technologies, leading to higher emission intensity; ii) well-designed environmental policies can mitigate these impacts. A case study using more granular data on Portuguese firms further shows that: iii) green investment is more elastic to financing conditions than other types of investment; iv) investment in integrated technologies is more sensitive to financing conditions and to managerial capacity compared to end-of-pipe solutions. Lastly, the paper discusses a wide range of policy options that may be considered to foster the green transition through upgrading firms' capacity